Bhutan Hydropower Sector Study : Opportunities and Strategic Options - World Bank (Washington, DC, 2014)
The objective of this study is to analyze the opportunities and strategic options available to the Royal Government of Bhutan (RGoB) to implement the hydropower projects included in its power master plan. It accounts for the relevant legal, technical, environmental, social and financial issues, as well as Bhutan's overall macroeconomic framework, and with full recognition that this resource is critical to Bhutan's economy. The scope of the study is to: (i) review and understand the framework for the existing agreement between India and Bhutan to finance the development of hydropower; (ii) review the power sector master plan to determine the competitiveness of planned projects, and their chances of being developed under a non-subsidized and/or private finance environment; (iii) review the options open to Bhutan in terms of power markets and trading; and (iv) propose some options for hydropower development in the medium to long term.